The Problematic Issue of Sharia Court's Absolute Authority under Indonesia Judicial System - Luthfiyah Trini Hastuti; Anti Mayastuti; Diana Lukitasari (Universitas Negeri Semarang, 2020)
The amendment of the Sharia Court position within the Indonesia’s public court jurisdiction is contained in Article 27 of Law Number 48 of 2009 concerning Judicial Powers where the existence of the Sharia Court is no longer stated to be included in the scope of the special court within this law. The amendment set different tone from what is contained in Law No. 4 of 2004 which in the elucidation of Article 15 states that, the Sharia Court is part of a special court. The problematic issue of Sharia Court's absolute authority in Aceh province under Indonesia judicial system is also the main study discussed in this article. At the end of the article, suggestions for improvement are also presented in order to strengthen the position of the Sharia Court in Indonesia judicial system.